Clinicopathological changes of the nervous system following inoculation of Pasteurella multocida B:2 and its immunogens in buffalo calves - Marza, Ali Dhiaa (2017)
Haemorrhagic septicaemia (HS) is an acute, highly fatal septicaemic disease affecting cattle and buffaloes with high morbidity and mortality rates. Pasteurellamultocida E:2 (African serotype) and B:2 (Asian serotype) are responsible of the disease in Africa and Asia, respectively. Despite continuing researches on thepathogenesis of P. multocida, the mechanisms by which these bacteria and its lipopolysaccharide (LPS) and outer membrane proteins (OMPs) immunogensdevelop the diseases are poorly understood. It is well known that HS affects mainly the respiratory and digestive tracts of cattle and buffaloes. However, involvement of other sites such as the nervous system in the pathogenesis of HS has been reported in previous studies, including outbreaks and pathogenesis studies of HS, without details. Therefore, this study was conducted to investigate in details the involvement of the nervous system towards P. multocidaB:2 and its lipopolysaccharides (LPS) and outer membrane proteins (OMPs) immunogens in buffalo calves. Twenty one clinically healthy, non-pregnant and non-lactating swamp buffalo calves were used in this study and divided into 7 groups of 3 buffaloes in each one.Buffaloes calves of group 1 (Ctrl) was inoculated orally with 10 ml of sterile phosphate buffered (PBS) as a negative control. Group 2 (Pmor) and group 3 (Pmsc) were inoculated with 10 ml of 1×1012cfu/ml of P. multocidaB:2 whole bacteriaorally and subcutaneously, respectively. Group 4 (LPSor) and group 5 (LPSiv) wereinoculated with 10 ml of LPS broth extracted from 1×1012cfu/ml ofP. multocidaB:2 orally and intravenously, respectively. Group 6 (OMPor) and group7 (OMPsc) were inoculated with 10 ml of OMPs broth extracted from 1×1012cfu/ml ofP. multocidaB:2 orally and subcutaneously, respectively. All calves in Pmor, LPSor, LPSiv and OMPor and Ctrl groups survived during the experiment and euthanized at the end of the experiment at 504 h (21 days) post inoculation, while calves in Pmsc and OMPsc groups had to be euthanizedafter 12 h and 72 h post infection, respectively as they develop sever clinical signs of HS according to the guideline of the Institutional Animal Care and Use Committee (IACUC). In order to monitor both general clinical and neurological responses during the experiment, detailed clinical examination were performed based on modified scoring system including; total general clinical score (TGCS) and total nervous clinical score (TNCS). The TGCS includes scores of mean rectal temperature (MRT), mean respiratory rate (MRR) and mean heart rate (MHR), in addition to scores of demeanour, appetite, nasal discharge and nature of respiration. While TNCS includes scores of mentation, gait abnormalities, fixation reflex, menace response, pupillary light reflex, perineal reflex, photomotor reflex, tongue tone test, gag reflex, swallowing reflex, panniculus reflex, pedal reflex, patellar reflex and palpebral reflex. In addition, pathophysiological changes in the cerebrospinal fluid (CSF) were also evaluated which include selected proinflammatory cytokines and acute phase proteins. After euthanization of the calves, complete post mortem, microbiological and histopathological examinations were conducted on the calves in the studies groups. Clinically, significant differences (P<0.05) in both TGCS and TNCS were found among the studies groups compare with Ctrl group. However, Pmsc and OMPscgroups developed severe clinical signs and recorded sharp increase in both TGCSand TNCS that lead to euthanization of the calves in these groups at 12 and 72 h post inoculation, respectively, and this indicates direct associated of increased nervous clinical signs with disease severity. While less severe TGCS and TNCS were recorded in Pmor, LPSor, LPSiv and OMP groups and calves in these groups were able to survive until the end of experiment at 504 h post inoculation, and this indicates that calves in these groups were able to overcome the infection with P. multocidaB:2 or inoculation of its LPS and OMPs immunogens. At necropsy, different levels of significance (P<0.05) in mean gross lesion score (MGLS) were recorded in buffalo calves in the studied groups including the cerebrum, cerebellum, brainstem and spinal cord when compared with calves of Ctrl group. However, the cerebrum and brainstem being the most affected sites of the nervous system. On the other hand, examination of the cranial and spinal nerves did not reveal any significant changes. The pattern of the pathological lesions reflect the severity of the clinical signs where Pmsc and OMPsc groups represented the per acute stage of the disease and congestion and hemorrhage in the brain and spinal cord were the most prominent lesions. However, oedema was noted in the brain of the buffalo calves in OMPsc rather than Pmsc group. While the pathological changes were different in LPSiv group in which oedema was more prominent than congestion and hemorrhage. Less MGLS were observed in the Pmor, LPSor and OMPor groups indicating the less effect of the oral route on the nervous system. Additionally, positive bacterial re-isolation and polymerase chain reaction (PCR) confirmation ofP. multocidaB:2 from different parts of the nervous system in calves of Pmsc groupconfirm the ability of these bacteria to cross blood brain barrier (BBB) especially at the per acute stage of the disease and support the involvement of the nervous system in the pathogenesis of HS. The histopathological examination of the nervous system of the inoculated groupsreflect the previously observed gross pathological findings, and significant increase (P<0.05) has been found in the total mean histopathological lesion score (MHLS) of the treated groups: Pmor, Pmsc, LPSor, LPSiv, OMPor and OMPsc when compared with calves of Ctrl group. The histopathological changes recorded in this study included; inflammatory cells infiltration, oedema and spongiosis, gliosis, congestion and hemorrhage, in addition to necrosis and degeneration and confirm the ability of P. multocidaB:2 and its LPS and OMPs immunogens to cross the BBB and induce their pathological effects. While the most affected sites of the nervous system were the cerebrum and brainstem. Although various histopathological lesion were reported in different parts of the nervous tissues, the route of inoculation was observed to play a significant role in determination of the severity of the lesion assubcutaneous and intravenous routes in Pmsc, OMPsc and LPSiv groups showed the most pronounced and higher lesion distribution than respected orally inoculated groups.Pathophysiological changes including; classical parameters, proinflammatory cytokines and acute phase proteins (APPs) also showed various levels of difference in the studied groups. Classical parameters showed significant differences (P<0.05) with high values recorded in the CSF total leukocytic count (CSF-TLC) and CSF total protein (CSF-TP) especially Pmsc and OMPsc groups as indication of acute body response to the disease produced. Significant increase also observed in the levels of CSF cytokines including; tumor necrosis factor-α (CSF-TNF-α), interleukins (CSF-IL-1) and (CSF-IL-6) in addition to CSF APPs including; haptoglobin (CSF-Hp), serum amyloid A (CSF-SAA) and C-reactive protein (CSF-CRP) concentrations which indicate that the subcutaneous route of inoculation would induce more severe reactions rather than oral route. According to presented evidences, it can be concluded thatP. multocidaB:2 and its LPS and OMPs immunogens were able to cross the BBB and induce pathological changes in different sites of the nervous system. The produced neuropathological changes could make alteration in animal behavior with the evidence of absence of some of the neurological responses especially in Pmsc and OMPsc groups, and this was supported by the increased concentrations of proinflammatory cytokines and APPs in the CSF in these groups. Accordingly, these results provide for the first time strong evidence of the involvement of the nervous system of buffalo calves experimentally inoculated of P. multocidaand its immunogens in the pathogenesis of HS, and shows that the type of inoculum and route of inoculation strongly affect the induced pathological changes of the nervous system and also the severity of disease produced.